Measuring air change rates using the PFT technique in Residential Buildings in Northern Portugal - M. Pinto (2006)
Portugal has technical recommendations and standards regarding ventilation rates in natural ventilation systems. However, these ventilation rates have not been fulfilled in most residential buildings recently erected in Portugal. We believd that natural ventilation systems alone are unlikely to guarantee the recommended ventilation, and so we characterized the performance of a mixed ventilation system consisting of an air inlet through self-a-adjustable inlets in bedrooms and living room, natural exhaust in bathrooms and fan exhaust systems in kitchens. We measured ventilation conditions in a residential complex of 94 apartments in the Porto area using the passive tracer gas method, more precisely the PFT technique. The study evaluates the façade's permeability and the respective air exchange rates per compartment using the PFT technique. Seven flats were analyzed, six of which have a mixed ventilation system (continuous exhaust system enabling the performance of the two systems to be compared. The experimental results allow, namely, the evaluation of the influence of insulation, a grid with low head loss and a static ventilator in the duct of the bathroom and the continuous exhaust ventilation in the kitchen. KEYWORDS: Ventilation, dwellings, air change rate (ACH), PFT